1973
DOI: 10.1172/jci107386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraduodenal Glucose Administration on Hepatic Extraction of Insulin in the Anesthetized Dog

Abstract: A B S T R A C T Extraction of insulin by the liver after administration of glucose in the duodenum has been studied in fourteen anesthetized dogs. Plasma insulin and glucose were measured in the portal vein hepatic vein and hepatic artery. During the control period 40 ±3% of the approximately 11 mU of insulin presented to the liver/min was removed during a single transhepatic passage. Within 5 min after glucose administration, the amount of insulin reaching the liver increased significantly. In some animals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 18 publications
9
60
0
1
Order By: Relevance
“…The values represent the function of the whole organ (not only of one of its vascular regions). The estimated amounts of IRI output for anaesthetized dogs are comparable to the calculations by indirect methods of other authors [11,20,44 [33] -2.5 mU/min (15 kg). Some of the values referred to were converted or they were taken from figures.…”
Section: Discussionsupporting
confidence: 83%
“…The values represent the function of the whole organ (not only of one of its vascular regions). The estimated amounts of IRI output for anaesthetized dogs are comparable to the calculations by indirect methods of other authors [11,20,44 [33] -2.5 mU/min (15 kg). Some of the values referred to were converted or they were taken from figures.…”
Section: Discussionsupporting
confidence: 83%
“…Reasons for this may include the fact that C-peptide and insulin antibodies have no cross-reaction [20] and that it does not undergo significant hepatic extraction [21,22]. Note, the liver is the major site of insulin metabolism, variably extracting ~50% of insulin delivered to it [23][24][25]. It has therefore been suggested that peripheral C-peptide levels more accurately reflect pancreatic insulin secretion rates than do peripheral insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin secreted from the B-cell reaches the liver, where about 50% of insulin is extracted and modulated, according to Madison and Kaplan (1958), Kaden et al (1973) and Mondon et al (1975). In contrast, as far as C-peptide is concerned, only a small part is handled in the liver and most of C-peptide is excreted from the kidney (Katz and Rubenstein 1973;Sherwin et al 1976;Rabkin et al 1978).…”
Section: Discussionmentioning
confidence: 99%